INDEKS DMF-T dan def-t MURID USIA 7-10 TAHUN MI TARBIYATUT THOLABAH LAMONGAN - Kurniawan, Hansen; Fitriani, Yufita; Sari, Rima Parwati; Handayani, Budi; Rahmitasari, Fitria; Prabowo, Puguh Bayu; Aprilia, Aprilia; Ariestania, Vivin; Priambodo, Nur Tsurayya; Saptaswari, Dianty (MAJU : Indonesian Journal of Community Empowerment, 2025)
Background Based on the 2018 Basic Health Research (Riskesdas), it was reported that the prevalence of dental and oral problems in Indonesia is still very high, namely 57.6 percent. Of this figure, only 10.20% have received treatment. Dental and oral health in Indonesia, especially in coastal areas, is still a complex problem. (Komarudin, Apriasari and Azizah, 2021) Lack of public attention and equal distribution of health facilities, especially in the field of Dentistry, are still factors that influence public understanding of dental and oral health. Dental and oral health status can be assessed using the DMF-T and def-t indices. Objective To assess the dental and oral health status in children aged 7-10 years MI Tarbiyatut Tholabah, Paciran Lamongan Method Dental and oral examination of children aged 7-10 years MI by assessing the DMF-T and def-t indices. Conclusion The results of the dental and oral examination of students at MI Tarbiyatut Tholabah, Paciran Lamongan with a def-t value of 2.71 which means the dental and oral health status with moderate results, and the DMF-T index with a result of 0.56 which means very low.